2006
DOI: 10.1111/j.1745-7254.2006.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

A long-form alpha-neurotoxin from cobra venom produces potent opioid-independent analgesia1

Abstract: Aim: In light of the antinociceptive activity of the short‐chain neurotoxin, cobrotoxin, and other acetylcholine antagonists, the antinociceptive activity and mechanisms of cobratoxin (CTX), a long‐chain postsynaptic α‐neurotoxin, was investigated in rodent pain models. Methods: CTX was administered intraperito‐neally (30,45, 68 μg/kg), intra‐cerebral ventricularly (4.5 μg/kg) or microinjected into periaqueductal gray (PAG; 4.5 μg/kg). The antinociceptive action was tested using the hot‐plate and acetic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 21 publications
0
47
1
1
Order By: Relevance
“…Cholinergic signals derived from vagus nerve stimulation inhibit the release of TNF, IL-1, HMGB1, and other cytokines by transducing cellular signals that inhibit the nuclear activity of NF-κB [38] . In contrast to the roles of nicotinic cholinergic receptors agonists discussed earlier, the present study indicates that CTX, which may be a nicotinic antagonist, also has a role in inflammatory relief [19,39] . As far as we know, no reports demonstrate that CTX interacts with any receptor other than AChR.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cholinergic signals derived from vagus nerve stimulation inhibit the release of TNF, IL-1, HMGB1, and other cytokines by transducing cellular signals that inhibit the nuclear activity of NF-κB [38] . In contrast to the roles of nicotinic cholinergic receptors agonists discussed earlier, the present study indicates that CTX, which may be a nicotinic antagonist, also has a role in inflammatory relief [19,39] . As far as we know, no reports demonstrate that CTX interacts with any receptor other than AChR.…”
Section: Discussioncontrasting
confidence: 99%
“…The analgesic effects of CTX were antagonized by atropine, but not naloxone. These results indicated that CTX produced potent opioid-independent analgesia [19] . Recently, we also found that CTX exhibited a dose-dependent analgesic action in formalin-induced phase 1 and phase 2 pain responses and inhibited enhancement of c-Fos-positive cells in the spinal cord (Liu et al, manuscript submitted).…”
Section: Introductionmentioning
confidence: 82%
“…Of the neurotoxins, the α-neurotoxins competitively bind to the postsynaptic neuronal and skeletal muscular nicotinic cholinergic receptors (nAChRs), leading to muscular paralysis (10). There is also evidence to show that some of the α-neurotoxins result in a centrally mediated opiate-independent analgesia through the nAChRs and can substitute morphine and mitigate opioid withdrawal (7,11). Given the role of nAChRs in rewarding or euphoric experiences associated with substance use mediated through the mesolimbic dopaminergic system, it seems plausible to assume that the pleasurable experiences described by our patients may be mediated by the same pathway (12).…”
Section: Discussionmentioning
confidence: 99%
“…The peak effect of analgesia was seen 3 h after CTX administration. Furthermore, naloxone failed to block the analgesic effects of CTX, but atropine did antagonize the analgesia mediated by CTX in the mouse acetic acid writhing test, indicating that the cholinergic, but not opioid system, appears to be involved in the antinociceptive action of CTX [8] . It is not currently known whether CTX inhibits inflammatory pain.…”
Section: Introductionmentioning
confidence: 90%